Perdebatan Antara Land Sharing dan Land Sparing - Fitri Wijayanti; Raudha Anggraini Tarigan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
The debate between Land Sharing and Land Sparing has been a significant debate in decision-making for several years. In decision-making, there are several things that must be considered, including social, economic, and ecological. However, over time, the increase in food is also increasing. In addition, another important thing is biodiversity which is a limiting factor in maintaining ecology. This article reviews the effectiveness of land-sharing and land-sparing selection from an agricultural point of view.